Probiotic potential and anti-quorum sensing activity of Enterococcus faecalis and Lactobacillus kunkeei isolates from Apis mellifera - Kiymaci, ME; Simsek, D; Tok, KC; Dirican, D; Gumustas, M (Journal of the Hellenic Veterinary Medical Society, 2023)
One health is an approach that gains importance in the protection of public health and advocates that the environment-animal-human health is linked. Microbial resistance occurring in any of these three factors circulates directly or indirectly between species and affects health. In this study, antimicrobial, anti-quorum sensing activity and potential probiotic properties of Lactobacillus acidophilus and Enterococcus faecalis 1 and 2 isolates from Apis mellifera gut were investigated. Results showed that isolates were found to be resistant to gentamicin, streptomycin, erythromycin, and clindamycin tested. It was determined that isolates were gamma haemolytic and resistant to acid and enzymatic environment conditions. Enterococcus faecalis isolates had antimicrobial activity on Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29212 and Pseudomonas aeruginosa ATCC 27853 and anti-quorum sensing activity of the culture supernatants of all isolates was detected by a violacein pigment inhibition of Chromobacterium violaceum strain.